2018
DOI: 10.1093/pm/pny095
|View full text |Cite|
|
Sign up to set email alerts
|

An Experimental Test of the Effectiveness of Unsolicited Reporting by a Prescription Drug Monitoring Program in Reducing Inappropriate Acquisition of Opioids

Abstract: Requiring prescribers to solicit patients' prescription histories is likely to be a more effective use of PDMP resources than proactive notification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…92,93 Six studies found that mandatory use of PDMPs, including unsolicited and proactive reporting of patient prescription histories, improved opioid-related outcomes. [94][95][96][97][98][99] ThesepositivefindingsonstrongPDMPswere notuniform:1studyfoundnosignificantassociationbetween mandatory use requirements and the number of opioid prescriptions among patients undergoing general surgical procedures 100 and another study found that strong and weak PDMPs were associated with similar changes in opioid prescription rates, the number of cumulative doses, and prescriptionlength(indays)amongMedicarebeneficiaries. 101 Studies published after our review period investigated GoodSamaritanlaws,painclinicandmarijuanaregulations, prescribing guidelines, and educational interventions.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…92,93 Six studies found that mandatory use of PDMPs, including unsolicited and proactive reporting of patient prescription histories, improved opioid-related outcomes. [94][95][96][97][98][99] ThesepositivefindingsonstrongPDMPswere notuniform:1studyfoundnosignificantassociationbetween mandatory use requirements and the number of opioid prescriptions among patients undergoing general surgical procedures 100 and another study found that strong and weak PDMPs were associated with similar changes in opioid prescription rates, the number of cumulative doses, and prescriptionlength(indays)amongMedicarebeneficiaries. 101 Studies published after our review period investigated GoodSamaritanlaws,painclinicandmarijuanaregulations, prescribing guidelines, and educational interventions.…”
Section: Discussionmentioning
confidence: 94%
“…emergency department visits resulting in opioid prescriptions or prescribed MME in Washington State. 42 These differences may have been the result of state PDMP characteristics, such as different methods of automated reporting and/or analytic designs (eg, the study of unsolicited PDMP reporting in Nevada used propensity score matching 33 ).PDMPeffectivenessmaychangeovertime:a 4-state study found an immediate decline in the percentage ofpersonsfillingopioidprescriptionsafterimplementation of robust PDMPs that mandate access, monitor multiple drug schedules, and update data regularly, but only 1 state saw a sustainedeffect. 28 Some evidence suggests that PDMPs result in increased heroin use, presumably because opioid users will substitute heroin for opioids.…”
Section: Impact Of Systems-level Interventions On Opioid Use Overdosmentioning
confidence: 99%
See 1 more Smart Citation
“…The extracted data from the included studies were then classified into main conceptual categories and summarised to align with the scoping review objective and research questions. The data extraction results are presented in Tables S1 and S2 [18–166], Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…Our findings are consistent with research that has found a reduction in risky prescribing practices after receipt of unsolicited reports from the PDMP. 54,55 However, proactive PDMPs were associated with higher rates of overdose from synthetic opioids other than methadone. The last period of study (2010-2016) coincided with a shift in the profile of the opioid overdose epidemic, so that illegally produced synthetic opioids such as fentanyl and related analogs broadly contaminated the illegal opioid supply and became the leading type of opioid involved in overdose deaths.…”
Section: Discussionmentioning
confidence: 99%